Empirical analysis of trade policy and institutional effects on growth - ARIF, Md. Shamsul (KDI School, 2015)
Trade and better institutional quality play a significant role in growth for developing countries in the long run. This research tries to find out the institutional and trade policy effects on growth in the long-run in the context of developing countries. Last two decades, some developing countries have achieved fast growth due to trade openness as well as institutional reform. This research estimated such indicators empirically using last three decades data of 58 developing countries. In order to estimate coefficient instrumental variable approach adopted and found significant effects of institutional indices on growth. Trade policy has effects on growth, but not significant. This research also investigated the decadal change in institution variables’ effects on trade using instrumental variable and found significant impact on trade.
Thesis(Master) --KDI School:Master of Development Policy,2015